Suppression Effects of Betaine-Enriched Spinach on Hyperhomocysteinemia Induced by Guanidinoacetic Acid and Choline Deficiency in Rats - Yi-Qun Liu; Zheng Jia; Feng Han; Takahiro Inakuma; Tatsuya Miyashita; Kimio Sugiyama; Li-Cui Sun; Xue-Song Xiang; Zhen-Wu Huang (The Scientific World Journal)
Betaine is an important natural component of rich food sources, especially spinach. Rats were fed diets with betaine or spinach powder at the same level of betaine for 10 days to investigate the dose-dependent effects of spinach powder supplementation on hyperhomocysteinemia induced by guanidinoacetic acid (GAA) addition and choline deprivation. The GAA-induced hyperhomocysteinemia in rats fed 25% casein diet (25C) was significantly suppressed by supplementation with betaine or spinach, and it was completely suppressed by taking 11.0% spinach supplementation. The choline deprivation-induced enhancement of plasma homocysteine concentration in rats fed 25% soybean protein diet (25S) was markedly suppressed by 3.82% spinach. Supplementation with betaine or spinach partially prevented the effects of GAA on hepatic concentrations of methionine metabolites. The decrease in activity of betaine-homocysteine S-methyltransferase (BHMT) and cystathionine β-synthase (CBS) in GAA-induced hyperhomocysteinemia was recovered by supplementation with betaine or spinach. Supplementation with betaine or spinach did not affect BHMT activity, whereas it partially restored CBS activity in choline-deprived 25S. The results indicated that betaine or spinach could completely suppress the hyperhomocysteinemia induced by choline deficiency resulting from stimulating the homocysteine removal by both remethylation and cystathionine formation.